Mediality on Trial (De Gruyter, 2025)
Insofar as one presumes a division between distinctly opposed categories of religion and the secular, technical media tend to be associated with the secular and human (trance) mediums tend to be associated with religion after 1900. This volume concerns the ways in which the term medium marks an overlapping of – and thus problematizes – the division between religion and the secular, the personal and the technological.